**CONCEPT: **Sum of the first n natural numbers =n(n+1)/2

**SOLUTION:**

-According to the question-

Sum of the first (x-1) natural numbers = Sum of natural number from (x+1) to 49.

So,

(x−1)(x)/2=(49×50)/2 - (x)(x+1)/2

⇒ 2x^2=49×50

⇒ x=7×5= 35 (C)

Modified on: Tue, 12 Oct, 2021 at 12:20 PM

**CONCEPT: **Sum of the first n natural numbers =n(n+1)/2

**SOLUTION:**

-According to the question-

Sum of the first (x-1) natural numbers = Sum of natural number from (x+1) to 49.

So,

(x−1)(x)/2=(49×50)/2 - (x)(x+1)/2

⇒ 2x^2=49×50

⇒ x=7×5= 35 (C)

Did you find it helpful? Yes No

Send feedbackSorry we couldn't be helpful. Help us improve this article with your feedback.

Help Desk Software
by Freshdesk Support Desk